The body politic has private parts: market creation as a policymaking tool - Sankaran, Kirun (Economics and philosophy, 2025)
Philosophical arguments about government contracting either categorically oppose it on legitimacy grounds or see it as largely anodyne. I argue for a normatively distinct kind of contracting – the advance market commitment, or AMC – and show that it is justified by the same liberal values that justify the welfare state.